KUALITAS KREDIT SEBAGAI PEMODERASI PENGARUH TINGKAT PERMODALAN TERHADAP PROFITABILITAS PADA PERBANKAN SYARIAH - Tri Rinawati (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2019)
Islamic banking is a financial institution that has a function as an intermediary betweenpeople who have excess funds and people who lack funds. Sharia banking operational activities arebased on Islamic economic systems that do not contain elements of gharar, maysir and usury. Shariabanking activities are expected to be an alternative solution in overcoming the problem of povertybecause in Islamic banking there are financial instruments in the form of zakat funds obtained fromcustomers who carry out financing and savings activities. In Islamic economic systems reject themotive of speculation and greedy behavior towards property which is a character of intrinsic lust forhumans who tend to love wealth.The purpose of this study is to determine the effect of capital as measured by the Capital AdequacyRatio (CAR) on Rentability (Earnings) as measured by Return On Assets (ROA) and Non PerformingFinancing (NPF) as moderating.Data sources are secondary data obtained from bank financial reports obtained fromwww.idx.co.id, and obtained from literature such as books, journals, and others related to research.The population is Islamic banks in Indonesia, totaling 12 banks. The method of determining thesample is saturated sampling with a population of less than 30 people. The sample that will be usedas a source of information in this study amounted to 12 banks. Data analysis methods used include (1)Test Descriptive Statistics. (2) Test of Multiple Regression Analysis. (3) Model Feasibility Test.From the results of testing the hypothesis, it can be concluded that Capital Adequacy Ratio has apositive effect on Return On Assets and with the Non Performing Financing (NPF) (moderatingvariable) will be able to strengthen the influence of the Capital Adequacy Ratio on Return On Assets.